2020
DOI: 10.1007/s10854-020-04002-5
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and pyroelectric properties of Mn-doped 0.36Pb(In1/2Nb1/2)O3–0.36Pb(Mg1/3Nb2/3)O3–0.28PbTiO3 ceramics

Abstract: Piezoelectric and pyroelectric properties as well as strain behavior of 0.5 mol% Mn-doped 0.36Pb(In1/2Nb1/2)O3-0.36Pb(Mg1/3Nb2/3)O3-0.28PbTiO3 (Mn-PIMNT) ceramics were studied. High piezoelectric coefficient of d33 = 235 pC/N, planar electromechanical coupling factor of kp = 43.1% and the high-power Figure of Merit (FOM = 60160 pC/N) were achieved in Mn-PIMNT ceramics. Furthermore, the ceramics exhibited high pyroelectric coefficient of p = 4.8×10-4 Cm-2 K-1 , figures of merit for the current responsivity of F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…0.5 mol% Mn‐doped Mn‐PIMNT(36/36/28) ceramic targets were fabricated by a conventional solid‐state reaction technique 20 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…0.5 mol% Mn‐doped Mn‐PIMNT(36/36/28) ceramic targets were fabricated by a conventional solid‐state reaction technique 20 …”
Section: Methodsmentioning
confidence: 99%
“…0.5 mol% Mn-doped Mn-PIMNT(36/36/28) ceramic targets were fabricated by a conventional solid-state reaction technique. 20 The conductive oxide SrRuO 3 (SRO) thin film was deposited on (111)-oriented SrTiO 3 (STO) single-crystal substrates by pulsed laser deposition (PLD) using a krypton fluoride (KrF) excimer laser with a wavelength of 248 nm. Then, Mn-PIMNT(36/36/28) thin films were deposited on SRO-buffered (111)-oriented STO substrates and the deposition conditions of SRO and Mn-PIMNT(36/36/28) thin films are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies indicated that ternary relaxor ferroelectric systems represented by Pb(In 1/2 Nb 1/2 )O 3 -Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PIMNT) and Pb(Mn 1/3 Nb 2/3 )-PbZrO 3 -PbTiO 3 were developed to simultaneously possess electromechanical properties and stable piezoelectric response. [13][14][15][16] Among them, the 0.06 Pb(Mn 1/3 Nb 2/3 )-0.94 Pb(Zr 0.48 Ti 0.52 )O 3 (PMN-PZT) aroused extensive attention due to the superior electromechanical properties as the composition was close to the MPB between rhombohedral (R) and tetragonal (T) phases. 17 High-quality PMN-PZT thin film was also developed on Pt-electrode MgO substrate with high ferroelectric polarization up to 100 μC/cm 2 and high Curie point.…”
Section: Introductionmentioning
confidence: 99%